Anti-thrombotic action of clopidogrel and PlA1/A2 polymorphism of β3 integrin in patients with coronary artery disease not being treated with aspirin - Dropinski, Jerzy; Musial, Jacek; Jakiela, Bogdan; Wegrzyn, Wojciech; Sanak, Marek; Szczeklik, Andrew (Thrombosis and Haemostasis, 2005)
Individual variability in response to clopidogrel is known but its mechanism is poorly understood. We examined the relationship between glycoprotein IIIa polymorphism PlA1/A2 and anti-thrombotic actions of clopidogrel. Clopidogrel (75 mg/d; 2 weeks) was administered to 48 normolipemic patients with coronary artery disease. Bleeding time, thrombin generation at the site of microvascular injury, platelet function under high shear, using PFA-100 with ADP cartridge, and platelet surface activation markers (P-selectin and fibrinogen binding sites on GPIIb/IIIa complex detected by PAC-1 antibody), were studied both before and after clopidogrel treatment. Both unstimulated and low-dose (0.02 μM and 1 μM) in vitro ADP-stimulated platelets were examined. GP IIIa polymorphism was assessed by polymerase chain reaction and restriction fragment length polymorphism analysis. We identified 32 PlA1/A1 homozygotes, 15 PlA1/A2 heterozygotes and one PlA2/A2 homozygote. Clopidogrel significantly prolonged bleeding time in all subjects, but this effect was greater in PlA2 carriers (p<0.01). Furthermore, clopidogrel only depressed thrombin generation at the site of microvascular injury (p<0.01) in PlA2 patients and prolonged closure time measured in vitro by PFA-100 (p<0.05). At baseline spontaneous expression of PAC-1 and P-selectin was higher in PlA2 subjects as compared to PlA1 homozygotes (p<0.05 for both antigens). Clopidogrel lowered the expression of both markers affecting more PlA2 carriers, so that the difference in binding PAC-1 antibody between platelets from PlA1 and PlA2 carriers disappeared, while the difference in P-selectin expression slightly diminished. Anti-thrombotic effects of clopidogrel are more pronounced in CAD patients carrying the PlA2 allele than in PlA1 homozygotes.
Keywords: Clopidogrel; coronary artery disease; glycoprotein IIIa polymorphism; platelet activation; thrombin generation